Experiences of health service providers establishing an Aboriginal-Mainstream partnership to improve maternity care for Aboriginal and Torres Strait Islander families in an urban setting. (December 2019) - Hickey, Sophie; Couchman, Katrina; Stapleton, Helen; Roe, Yvette; Kildea, Sue
Highlights: Australian policy encourages partnerships between Aboriginal and Torres Strait Islander community-controlled health organisations and mainstream health services to improve health service delivery to Aboriginal and Torres Strait Islander people. Service planners remain unsure about how to best implement such partnerships in maternity care, and there is a lack of appropriate tools designed to gauge the state of such partnerships for the Australian Indigenous context. This study found perceptions of the state of the partnership was subjective to role type for staff establishing one such new partnership already showing improved health outcomes. Staff involved in management and strategic planning were more like to report a positive partnership, with service delivery staff reporting more challenges translating the vision into practice. We discuss our action research responses to address some of these challenges in practice. We provide suggestions for future evaluators reviewing the state of Aboriginal-Mainstream Partnerships, in particular the utility ofBurton's (2012) Eight Principles for Genuine and Sustainable Aboriginal-Mainstream Partnerships, to be used in conjunction with general collaborative partnership and change management literature, towards capturing the diverse and dynamic contexts of these partnerships. Abstract: Australian policy encourages multiagency partnerships between hospitals and Aboriginal Community Controlled Health Organisations to improve the health of Aboriginal and Torres Strait Islander people. Service planners remain unsure about how to implement such partnerships in maternity care, and there is a lack of appropriate tools designed to gauge the state of such partnerships for the Australian Indigenous context. In 2013, two Aboriginal health services and a major tertiary hospital partnered to deliver best practice maternity care to Indigenous families in Brisbane, Australia. A participatory action research approach underpinned this study. Semi-structured qualitative interviews and focus groups were conducted with 21 of the partnership staff. All interviewees emphasized the partnership's commitment to improving long-term health and wellbeing for Indigenous families. Strategic planners were more likely to report a positive partnership than staff involved in service delivery who had diverse views. This highlights the challenges of change management when conducting such a significant service redesign in this cross-cultural context. We detail changes made within the partnership in response to the findings and provide suggestions for future development of an evaluation tool to review the state of Aboriginal-Mainstream Partnerships.